HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEJADIAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Setia Nisa; Rika Armalini; Welly Handayani; Resi Citra M; Yohana Suganda (Ensiklopedia Education Review, 2025)
Emesis gravidarum is a common condition characterized by nausea and vomiting during pregnancy, particularly in the first trimester, which can affect maternal health and quality of life. This study aimed to determine the relationship between knowledge and attitudes of pregnant women and the incidence of emesis gravidarum in the working area of Puskesmas Limau Purut, Padang Pariaman Regency, in 2024. A cross-sectional design was used with a total of 36 first-trimester pregnant women selected through purposive sampling. Data were collected using a structured questionnaire covering aspects of knowledge, attitudes, and the incidence of emesis gravidarum. The chi-square test with a significance level of 0.05 was applied for statistical analysis.The results showed that 55.6% of respondents experienced moderate emesis gravidarum. A total of 50% of respondents had poor knowledge levels, and 58.3% displayed negative attitudes toward the management of emesis gravidarum. Statistical analysis indicated no significant relationship between knowledge and the incidence of emesis gravidarum (p = 0.685), but a significant relationship was found between attitudes and the incidence of emesis gravidarum (p = 0.023).In conclusion, there is a significant relationship between pregnant women’s knowledge and attitudes and the incidence of emesis gravidarum in the first trimester. Strengthening health education and support for pregnant women is essential to reduce the incidence of emesis gravidarum and improve maternal quality of life during pregnancy.Keywords: Knowledge; Attitude; Emesis Gravidarum